Productivity, factor accumulation and economic policy: the case of Korea and Singapore - Fuentes, Rodrigo (Estudios de Economía, 2016)
This paper adressess growth measurement within the traditional growth accounting framework, by relating growth in labor productivity and growth in total factor productivity (TFP) to economic policies. Additionally, the relationship between TFP and measurement of human capital and scale economies was analyzed. The study was conducted by studying two developing countries, Korea and Singapore, characterized by an outward orientation of their economies. In Korea, which followed diversified and flexible strategies export promotion, productivity growth seemingly was due to scale economies and human capital accumulation, whereas in Singapore, an entrepot-based re-export economy, productivity growth was almost zero. The high growth in Singapore in seemingly originated by factor accumulation rather than by an increase in productivity. The low productivity growth was presumably due to comparative advantages in assembly-type activities, resulting from the immigration of low skilled labor from neighboring countries. In short, the paper emphasizes the paramount importance of factor measurement, manufacturing industry structure, economic policy, human capital accumulation and productivity as key issues to attain economic growth.